Securitization and Structured Finance in the RA - Minasyan, Lusine (Bulletin of Yerevan University G: Economics, 2022)
Securitization of financing transactions in which companies sell rights to payment under mortgage, loans, accounts receivable, lease rentals, or other types of income-producing, financial assets to a trust or other special-purpose vehicle (an “SPV” sometimes interchangeably called a special-purpose entity or SPE). The goal is to separate these assets from the risks generally associated with the company. The company then can use these assets to raise funds in the capital markets at a lower cost than if the company, with its associated risks, had borrowed the funds. Structured finance in the RA is regulated by the Laws of the RA “On Asset Securitization” and “Laws on Secured Mortgage Bonds”. As of 2021, in the RA, within the framework of the current legislative norms, several releases have been implemented according to two models. Considering securitization as one of the best legal mechanisms in the financial system, however in the face of current challenges, regulators face new challenges that require legal regulation.
Keywords: securitization funds; SPV; funds; fund manager; group of assets; securitization; mortgage bonds; investor; income